The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0093298
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Behavioral Changes during Confinement in a 520-Day Simulated Interplanetary Mission to Mars

Abstract: Behavioral health risks are among the most serious and difficult to mitigate risks of confinement in space craft during long-duration space exploration missions. We report on behavioral and psychological reactions of a multinational crew of 6 healthy males confined in a 550 m3 chamber for 520 days during the first Earth-based, high-fidelity simulated mission to Mars. Rest-activity of crewmembers was objectively measured throughout the mission with wrist-worn actigraphs. Once weekly throughout the mission crewm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 28 publications
6
107
0
1
Order By: Relevance
“…It is noticeable that this change occurred simultaneously as several crew members reported feeling less motivated, more depressed and irritable. An increase in depressive symptoms and psychological distress in the second half of the confinement are consistent with findings by other research groups [28,29]. A progressive decrease in positive emotions was also found during the previous 105-days confinement [30] and during Russian space missions [31].…”
Section: Alterations In Personal Valuessupporting
confidence: 90%
See 2 more Smart Citations
“…It is noticeable that this change occurred simultaneously as several crew members reported feeling less motivated, more depressed and irritable. An increase in depressive symptoms and psychological distress in the second half of the confinement are consistent with findings by other research groups [28,29]. A progressive decrease in positive emotions was also found during the previous 105-days confinement [30] and during Russian space missions [31].…”
Section: Alterations In Personal Valuessupporting
confidence: 90%
“…Potential bias in under-reporting negative symptoms during the mission has been noted also by other researchers [28]. In this study, this limitation seemed to be particularly linked with responses to part 3 of the PCVQ in which the crew members were asked to indicate tension which they attributed to individual differences in values.…”
Section: Methodological Limitationsmentioning
confidence: 76%
See 1 more Smart Citation
“…With the aim of reaching distant planets, it is necessary to gather data on human feelings and mental state in isolated situations. Studies have looked at situations of isolation lasting over a year [15]. Data on mental states in isolation have led to improvement in preparative procedures for scientists, whether sailors or other, before long term isolation on expeditions, boat races or other missions.…”
Section: Discussionmentioning
confidence: 99%
“…Our species evolved in a natural world, not in an unnatural man-made built environment. A simulated interplanetary mission to Mars study of six men in an analog environment revealed a diversity of behavioral responses (Basner et al, 2014) with some individuals exhibiting very modest changes, and at least one individual with increasingly more severe behavioral health decrement over time. As we evolved in a 1g world, living in a microgravity environment poses physiological and physical health challenges for flight crews that can negatively impact psychological wellbeing such as space motion sickness, shifts in body fluid distribution, and vestibular dysfunction (Williams et al, 2009) (Wilson, 1984), then people have an "innate tendency to focus on life and lifelike processes," and in a broader sense this could be taken to mean we have evolved with an innate need to be in and experience nature.…”
Section: Spaceflight and Stressmentioning
confidence: 99%